The Discourse of Hospital Communication
XVI, 275 p.
Keywords: Bringing together recent international research in the field of hospital communication and interaction, the contributors to this book contextualize clinical professional work by focussing on the rising intensity of information and communication practices in organizations generally, and in health care in particular.